2020
DOI: 10.1038/s42004-020-00402-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of molecular conformation and the incorporation of adatoms in an on-surface Ullmann-type reaction

Abstract: The on-surface synthesis of covalently bonded materials differs from solution-phase synthesis in several respects. The transition from a three-dimensional reaction volume to quasi-two-dimensional confinement, as is the case for on-surface synthesis, has the potential to facilitate alternative reaction pathways to those available in solution. Ullmann-type reactions, where the surface plays a role in the coupling of aryl-halide functionalised species, has been shown to facilitate extended one- and two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 45 publications
5
21
0
Order By: Relevance
“…Their coexistence indicates an incomplete polymerization reaction at this stage and implies that the formation of the Kagome lattice is governed by the formation of organometallic intermediates 2 . This observation is typical of hierarchical Ullman polymerization which has been corroborated in previous works using X‐ray photoelectron spectroscopy [24, 27, 28] . A final annealing to T 3 =220 °C promotes only the N‐KG 3 as observed by AFM (Figure 2 d), indicative of a complete polymerization reaction.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Their coexistence indicates an incomplete polymerization reaction at this stage and implies that the formation of the Kagome lattice is governed by the formation of organometallic intermediates 2 . This observation is typical of hierarchical Ullman polymerization which has been corroborated in previous works using X‐ray photoelectron spectroscopy [24, 27, 28] . A final annealing to T 3 =220 °C promotes only the N‐KG 3 as observed by AFM (Figure 2 d), indicative of a complete polymerization reaction.…”
Section: Methodssupporting
confidence: 86%
“…Compared to the surrounding carbon rings, [4,26] the PZQ moiety is identified by a darker and more elongated contrast as confirmed by AFM simulations ( Figure S4b This observation is typical of hierarchical Ullman polymerization which has been corroborated in previous works using X-ray photoelectron spectroscopy. [24,27,28] A final annealing to T 3 = 220 8C promotes only the N-KG 3 as observed by AFM (Figure 2 d), indicative of a complete polymerization reaction. Phenazine-based molecules and nanographene have shown thermal stability up to 500 8C.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In comparison to the debrominated TBQP molecules that always lie flat, twisted PZQ bridges in the N‐KG (Figure 1 d and black arrow in Figure 2 d) are systematically observed using the high vertical precision of AFM measurements [31] . This suggests a substantial mechanical stress in the Kagome structure as a result of polymerization [28, 32] …”
Section: Methodsmentioning
confidence: 83%
“…We considered coupling of a dimer in which the OM Cu is assumed to be an adatom, but found that ejection of the adatom during coupling involves an excessively high barrier of approximately 2.4 eV. The origin of the source of bridging metal atoms is still unsettled [25] and we thus followed the approach of lifting surface atoms. [12a,26] We found that dimerization along [1 −1 ±1] occurs via two elementary steps (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%